Effect of kinesio taping intervention on the muscle strength and balance of college basketball players with functional ankle instability - Li, Rui; Qin, Rui; Tan, Yajun; Liu, Hengxian; Wang, Kun; Cheng, Liang (Frontiers in Physiology, 2023)
Abstract: Objective: This study aimed to investigate the effects of acute Kinesio Taping (KT) on muscle strength and balance in college basketball players with functional ankle instability (FAI). Methods: A total of 30 college basketball players with FAI were treated with an acute KT to test the changes in their muscle strength and balance ability. Results: After the intervention of an acute KT, the ankle dorsiflexion moment and the ankle plantar flexion moment increased by 34% and 19.9%, respectively. The test of a stable plane with eyes open decreased by 1%, whereas the test of a stable plane with eyes closed decreased by 1.1%, meanwhile, the test of a swaying environment with eyes open increased by 2.4%, and the test of swaying plane with eyes open increased by 5.1%, whereas the test of swaying plane with eyes closed increased by 16.2%, and the test of swaying environment with eyes open + plane increased by 12.1%. Conclusion: From the results, this study shows that KT can increase the isokinetic strength of ankle dorsum muscle and plantar flexion of FAI college basketball players. In static balance test, KT has weaker effect on FAI college basketball players than dynamic balance test. It shows that KT can significantly improve the balance ability of FAI college basketball players during dynamic sports.